The Legal Dimensions of Communication in Hospital Settings: A Medicolegal Perspective - Muhammad Luthfie Hakim; Aby Maulana; Mizna Sabilla (Jurnal Hukum Replik, 2025)
Communication in healthcare services is not merely a technical or interpersonal matter, but an integral part of the legal and ethical responsibilities of the medical profession. This article aims to examine the legal aspects of communication in hospitals through a normative and analytical approach. The discussion focuses on the classification of communication types (clinical and administrative), effective communication methods (SBAR and closed-loop), and the strategic role of medical records in documenting explanations and informed consent. By tracing the provisions of Law Number 17 of 2023 on Health, related ministerial regulations, and field practices, this paper shows that communication and documentation failures are among the main causes of medical disputes in Indonesia. It also identifies common documentation errors, such as incomplete information, undocumented explanations, or explanations delivered by unauthorized personnel. The article concludes that effective and well-documented communication not only protects patient rights but also strengthens the legal standing of medical professionals and hospitals. Reforming communication and documentation systems in healthcare facilities should be an integral part of quality improvement and legal protection strategies in medical practice.